Breaking the Narrative: Feminist Retellings of Nepalese Women’s Struggles in Contemporary Fiction - Katuwal, Saraswati (Mindscape: A Journal of English & Cultural Studies, 2024)
This study analyzes feminist retellings in Niharika Karki’s Yogmaya (2018), Chreeharan (2019), and selected short stories from Women, War, and Violence in Select Fiction from Nepal, edited by Sushma Joshi (2022). These works reimagine Nepalese women’s struggles against genderbased violence, caste oppression, and patriarchal constraints, situating them within contemporary debates on gender equality. Despite women occupying 33 percent of parliamentary seats, national data reveal persistent challenges: 11.4 percent of women aged 15-49 experience gender-based violence, while discriminatory citizenship laws disproportionately exclude Dalit and Madheshi women. Against this backdrop, the selected texts challenge cultural silences by foregrounding resistance, intersectionality, and agency. Yogmaya reconstructs the defiance of a poet-activist who fought patriarchal customs and caste hierarchies; Chreeharan reinterprets Mahabharata figures like Draupadi to highlight resistance against sexual violence; and Joshi’s stories depict women’s resilience in the aftermath of war. Together, these narratives disrupt patriarchal stereotypes and resonate with feminist activism, including digital campaigns such as #NepalFeminism. By bridging literature, activism, and policy discourse, this paper highlights the role of Nepali fiction in advancing Sustainable Development Goal 5 (SDG 5). on gender equality and asks: How do feminist retellings reframe Nepalese women’s struggles, and what insights do they offer for addressing post- 2025 gender equality challenges?